2014
DOI: 10.1364/oe.22.005410
|View full text |Cite
|
Sign up to set email alerts
|

Background clean-up in Brillouin microspectroscopy of scattering medium

Abstract: Abstract:Brillouin spectroscopy is an emerging tool for microscopic optical imaging as it allows for non-contact, non-invasive, direct assessment of the elastic properties of materials. However, strong elastic scattering and stray light from various sources often contaminate the Brillouin spectrum. A molecular absorption cell was introduced into the virtually imaged phased array (VIPA) based Brillouin spectroscopy setup to absorb the Rayleigh component, which resulted in a substantial improvement of the Brillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

8
0

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 23 publications
0
55
0
Order By: Relevance
“…The major challenge in Brillouin spectroscopy of biological systems is eliminating the large amount of elastic scattering, which makes it difficult to identify a weak Brillouin peak. We recently reported that this limitation can be overcome by using a molecular/atomic gas cell as a notch filter [13]. Utilizing these advancements, we demonstrate simultaneous Raman-Brillouin microscopy, a potent new tool for bioimaging and analytical characterization.…”
Section: Fundamental Light-matter Interactions and Spectroscopy Of Bimentioning
confidence: 93%
“…The major challenge in Brillouin spectroscopy of biological systems is eliminating the large amount of elastic scattering, which makes it difficult to identify a weak Brillouin peak. We recently reported that this limitation can be overcome by using a molecular/atomic gas cell as a notch filter [13]. Utilizing these advancements, we demonstrate simultaneous Raman-Brillouin microscopy, a potent new tool for bioimaging and analytical characterization.…”
Section: Fundamental Light-matter Interactions and Spectroscopy Of Bimentioning
confidence: 93%
“…The experimental set-up based on the VIPA-based Brillouin spectrometer follows the description of Meng et al [24]. Fig.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Compared with conventional scanning Fabry-Perot interferometers, VIPA spectrometers enable better signal-to-noise ratio over a shorter acquisition time while maintaining good spectral resolution [5]. Moreover, with the application of atomic/molecular absorption cells and some other strategies, Meng et al developed background free Brillouin spectrometers, which substantially reduced the contaminations from elastic scattering induced by turbid samples [24,25]. However, weak signals are still difficult to detect in the presence of strong background.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with the application of atomic/molecular absorption cells, Meng et al developed backgroundfree Brillouin spectrometers, further reduced the contaminations from elastic scatterings induced by turbid samples. 21 However, the weak signal is still highly possible to be immersed in the background. This becomes a signi¯cant issue when imaging turbid biological tissues.…”
Section: Introductionmentioning
confidence: 99%